A dual‐band and wideband omnidirectional circularly polarized antenna based on VO2. Issue 3 (21st January 2019) - Liu, Guo‐Biao; Huang, Tong; Zhang, Hai‐Feng; Zeng, Li
Abstract: In this article, a dual‐band and wideband omnidirectional circularly polarized (CP) antenna based on the vanadium dioxide (VO2 ) is investigated. The operating bandwidth of such an antenna can be regulated by altering the outside temperature ( T ), which is attained by the insulator‐metal transition of VO2 . The omnidirectional CP antenna is based on a loop antenna‐dipole model, which is composed of four tilted metal and VO2 resonant units that are loaded around a cuboid and a feeding network for broadening bandwidth. The simulated results show that when T  = 50°C (State I), the 10‐dB impedance bandwidth is 45.7% (1.67‐2.66 GHz), and the 3‐dB axial ratio (AR) bandwidth is 40% (1.9‐2.85 GHz). When T  = 80°C (State II), the 10‐dB impedance bandwidth is 13.8% (1.62‐1.86 GHz), and the 3‐dB AR bandwidth is 21.8% (1.68‐2.09 GHz). In order to further characterize the concept of the proposed antenna, the related parameters of such an antenna are studied using simulation software HFSS.